一樣軌跡兩樣情：美國與我國師資培育機構轉型與教師質量之比較 Similar Routes but Different Paths: Teacher Preparation, Teacher Quantity and Quality in the U.S. and Taiwan - 黃源河 Yuanher Robin Hwang; 符碧真 Bih-Jen Fwu (National Taiwan Normal University, 2010)
隨著國際化浪潮興起，比較研究日漸受到重視。過去比較研究著重各國制度與實務的比較，近來採文化比較角度，探究形成制度與實務背後的社會文化脈絡。本文比較美國與我國師資培育機構轉型與教師質量，結果發現，兩國師資培育機構形式發展的歷史軌跡雖然相似，但是師資的「質」與「量」卻大異其趣。美國長久以來深陷教師數量不足及素質低落的困境，而我國則是教職出缺、競爭者眾，素質相對優秀，亦即「一樣軌跡兩樣情」。美國教師社會地位低落、薪資微薄，故難招募足夠數量的優秀師資；我國教師社會地位、薪資相對較優，故能吸引優質教師。追本溯源可能與西方「教僕文化」及我國相對應之「聖賢文化」密切相關。 Under the influence of globalization, the focus of comparative education has shifted from the traditional approach of comparing national systems or practices between countries to a more in-depth perspective of the underling socio-cultural contexts of the systems or practices. This study compares the historical development of teacher training institutions as well as teacher quantity and quality in two countries of interest, the United States and Taiwan, with stress on the socio-cultural frameworks that shape their teachers. The results show that the historical development of American and Taiwanese teacher training institutions has followed a similar route, but teacher quantity and quality between these two countries have been quite different. The US has long suffered serious teacher shortage and poor teacher quality, whereas Taiwan has successfully recruited and retained enough quality teachers. While meager salary and low social status of teachers in the US may have led to teacher shortage and poor teacher quality, the relative high salary and social status in Taiwan may have successfully attracted enough high quality teachers. Social cultural contexts of these two countries probably have contributed to the significant different incentives to attract quality teachers.